APPLICATION OF THE INQUIRY BASED ICARE LEARNING MODEL TOWARD COGNITIVE LEARNING OUTCOMES ON SALT HYDROLYSIS MATERIAL - Sabila Fatkhi, Sakina Elok; Solihah, Mar'attus (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
The implementation of chemistry learning that is teacher centered and the lessons are in the last hour making students lack concentrated so that it is difficult to understand the material delivered by the teacher, one of which is salt hydrolysis. This makes the test results of many students who have not reached the minimum completeness criteria (KKM) of the school is 70. Therefore, the purpose of this study is to find out differences in cognitive learning outcomes between students SMA N 01 Godong who used the inquiry-based ICARE model and the conventional model on salt hydrolysis material after being controlled by initial abilitiy (pre test). This study used a randomized pretest-posttest control group design and cluster random sampling. Data collection techniques using tests, observation, documentation, and interviews. The research data were analyzed using covariance analysis (anakova). Based on the results of the study, it was found that there were differences in cognitive learning outcomes that significant between the application of the inquiry-based ICARE learning model with conventional models after controlling the initial ability (pre-test) indicated from the sig value. 0.000. The value is smaller from 0.05 so that Ha of the study was accepted. The results can be concluded that the inquiry-based ICARE learning model can be used to make students' cognitive learning outcomes better than conventional learning models.